Nanoscale characterisation of soot particulates from gasoline direct injection engines - Pfau, Sebastian A. (2021)
Understanding the intricacies of particulate emissions from internal combustion engines is important due to their harmful impact on human health and the environment, as well as their contribution to engine wear and performance. Particulate emissions were historically associated with diesel engines which are predominantly using direct-injection systems. Thus, diesel soot is widely covered in the literature. However, the increasing market share of vehicles with gasoline direct-injection (GDI) engines over recent years raises the question of how GDI soot compares to diesel soot and if existing knowledge can be applied. The aim of this work was to close this gap in knowledge between GDI and diesel engine soot.